Effect of aspect ratio subjected to wind hazard in tall buildings situated along the coastal line of India. (8th February 2022) - Ghosh, Tamal; Sil, Arjun
Summary: The escalating growth of the tall buildings as well as the increasing number of extreme wind events in the Indian coastal region have certainly arisen the question of the safety and stability of these buildings situated in the metropolitan cities along the coastline. In such a scenario where there have been a constant focus on more researches for a unified wind code, however a comprehensive comparative study is required not only to assess and analyze the dynamic peak factors of the tall building models due to wind load, but also to enlighten the differences in the obtained results as well as their patterns respectively. The aspect ratio of buildings essentially governs the stability as well as contributes to a great extent on the dynamic responses in terms of base shear, base moment and torsional effects at the base. However, a framework based on the Indian wind database could ease the complexity of such parametric survivability studies of such structures. Distinguished variations in the dynamic responses for a series of models of tall buildings with varying aspect ratios along the height are analyzed as well as discussed in the present study, and the pattern of the deviation of the results with a parallel framework is also addressed to propose a mechanism for assessing the behaviors of tall buildings under specific wind speed predominant in the Indian coastal region that would help to ensure the safety and stability of structures subjected to wind hazards in Indian context in future.